Fomepizole as an adjunct in acetylcysteine treated acetaminophen overdose patients: a case series. (3rd April 2022) - Link, Stephanie L.; Rampon, Garrett; Osmon, Stephen; Scalzo, Anthony J.; Rumack, Barry H.
Abstract: Introduction: Acetaminophen (N-acetyl-para-aminophenol or APAP) is the leading cause of acute liver failure worldwide. Standard therapy for APAP overdose is with IV N-acetylcysteine (NAC). However, overdose patients treated with NAC can still incur hepatotoxicity in some circumstances. Fomepizole has proven safety in methanol and ethylene glycol poisoning and is a potent CYP2E1 and c-Jun-N-terminal Kinase (JNK) inhibitor that is effective even in the metabolic phase. Methods: We present a prospective case series of 14 consecutive, high-risk patients who had elevated APAP levels after overdose who were treated with fomepizole as an adjunct to standard IV-NAC. The attending toxicologist utilized clinical judgement to determine the use of fomepizole, especially if APAP levels persisted due to altered half-life or risk factors for toxicity. Results: There were no unfavorable outcomes in any patient, which were better than expected. Conclusions: This case series has demonstrated the safety of fomepizole in high-risk APAP overdose. The efficacy of fomepizole needs to be further elucidated through controlled clinical trials on a larger scale. In massive APAP overdoses, fomepizole should be considered as an adjunct due to the known failure rate of NAC and the safety profile of fomepizole.